Oral health behaviours of parents and young children in a practice‐based caries prevention trial in Northern Ireland. Issue 3 (22nd December 2017) - O'Malley, Lucy; Worthington, Helen V.; Donaldson, Michael; O'Neil, Ciaran; Birch, Stephen; Noble, Solveig; Killough, Seamus; Murphy, Lynn; Greer, Margaret; Brodison, Julie; Verghis, Rejina; Tickle, Martin
Abstract: Objectives: The NICPIP trial evaluated the costs and effects of a caries prevention intervention delivered to 2‐ to 3‐year‐old children attending dental practices in Northern Ireland. This supplementary study explored the oral health behaviours of children and their parents to help understand the reasons for the trial's findings. Methods: A mixed methods study that included a questionnaire completed by all parents (n = 1058) at the time they brought their child for the NICPIP final clinical assessment. The questionnaire collected data on frequency of toothbrushing and sugar consumption. Questionnaire data were analysed by trial group and caries status. Parents of trial participants (n = 42) were invited to take part in telephone interviews. Parents were purposively sampled according to trial group and whether or not their child developed caries. The interviews explored how and why oral health behaviours happened. Interview data were audio‐recorded, transcribed verbatim and analysed thematically. Results: The questionnaire data indicated that toothbrushing and between‐meal sugar snacking were common in the majority of children. The children of parents who automatically reminded their child to brush their teeth were more likely to remain caries‐free (Odds Ratio 1.24; 95% CI 1.08, 1.41; P  = .002). Frequency of sweet drink consumption was associated with the child developing caries (Odds Ratio 0.88; 95% CI 0.79, 0.98; P  = .021). The interview data showed that parents had positive attitudes towards brushing both in terms of perceived importance and expected outcomes. Attitudes towards sugar snacking were more complex, with parents reporting difficulties in controlling this behaviour. Sugar was described as being something that was "ever present" in children's lives. Conclusions: Toothbrushing was widely adopted from a young age, but between‐meal sugar consumption was highly prevalent. The results suggest that effective family‐level and population‐level interventions are needed to reduce sugar consumption if substantial improvements in caries prevention are to be achieved.